Analisis Eksergi Pada Ruang Bakar Pada Pltg Teluk Lembu 20 MW - Miswandi, Miswandi; martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Performance evaluation of the power plants is used by applying the first law of thermodynamics, but this method can not determine the source of irreversibilities. Irreversibility is the factor that caused a process to be irreversible. it is necessary to used exergy analysis. Performance of gas Turbine power plant is evaluated with exergy analysis is very useful in terms of design, evaluation, optimization and improvement of power plant. The result showed that the highest exergy destruction occurred in the combustion chamber reached 21,98 MW (85,21%) and while compressor is the lowest 3,81 MW(14,79%)Based on the calculation, analysis of exergy can determine magnitude, location of the exergy destruction. These will make it easier to conduct optimizations toincrease efficiencyKeywords: Gas turbine power plant, combustion chamber, exergy destruction